2020
DOI: 10.1038/s41467-020-16240-6
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and agricultural intensification destabilize animal communities differently than diversity loss

Abstract: Despite growing concern over consequences of global changes, we still know little about potential interactive effects of anthropogenic perturbations and diversity loss on the stability of local communities, especially for taxa other than plants. Here we analyse the relationships among landscape composition, biodiversity and community stability looking at time series of three types of communities, i.e., bats, birds and butterflies, monitored over the years by citizen science programs in France. We show that urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 63 publications
3
50
4
Order By: Relevance
“…Species richness has been found to increase primary productivity, community biomass and its temporal stability in various ecosystems and taxa, both experimentally and in natural settings (Cardinale et al, 2002;Franssen et al, 2011;Grace et al, 2016;Houlahan et al, 2018;Olivier et al, 2020;Pennekamp et al, 2018;Tilman et al, 1996Tilman et al, , 2006. However, these studies mainly focused on communities composed of a single trophic level, generally primary producers, thereby ignoring the potential effects of food-web structure (but see Scherber et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Species richness has been found to increase primary productivity, community biomass and its temporal stability in various ecosystems and taxa, both experimentally and in natural settings (Cardinale et al, 2002;Franssen et al, 2011;Grace et al, 2016;Houlahan et al, 2018;Olivier et al, 2020;Pennekamp et al, 2018;Tilman et al, 1996Tilman et al, , 2006. However, these studies mainly focused on communities composed of a single trophic level, generally primary producers, thereby ignoring the potential effects of food-web structure (but see Scherber et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Those that occupy very limited geographic distributions likely will become extinct. Olivier et al [48] point out that two major drivers of habit degradation are urbanization and agricultural intensification which decrease community stability, including bats.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, artificial lighting and sound pollution can alter commuting processes in foraging bats, especially sound which has a more deterrent effect for bats than light as some insectivorous bats feed on the insects that are attracted to streetlights [50][51][52]. Interestingly, habitat degradation affects the diversity of bat communities in more complex ways than simply population stability [48].…”
Section: How Urbanization Is Affecting Bat Diversitymentioning
confidence: 99%
“…We identified a list of the top 20 keywords for each time window based on the direction given by the previous study [20], which revealed that the term "urbanization" has steadily been mentioned throughout the evolution of UES research. Not surprisingly, many parts of the world are still being urbanized, which affects both the quantity and quality of ecosystem services at all scales in the 21st century [30,31]. Indeed, the central crisis of our time is to cope with the double-edged sword of urbanization [32].…”
Section: Discussionmentioning
confidence: 99%